2007 1st International Conference on Bioinformatics and Biomedical Engineering 2007
DOI: 10.1109/icbbe.2007.289
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Magnetite Nanoparticles Synthesis and Their Thermal-Stability

Abstract: Monodisperse magnetite (Fe 3 O 4 ) nanoparticles (MNPs) of 25±5 nm were prepared by modified chemical co-precipitation, and they were characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) with the energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), thermogravimetry analysis (TGA), X-ray photoelectron spectroscopy (XPS) and magnetic property measurement system (MPMS). The MNPs properties and structure were investigated thoroughly, particularly for their th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…The exothermic signal at 516 • C is attributed to the transformation from maghemite to hematite (␣-Fe 2 O 3 ). These two thermal events are consistent with the previously reported phase-transformation temperature range of magnetite [41,43,44]. As compared to Mag, MagMt-P exhibits much weaker signals of the transformation from magnetite to maghemite, which begins at about 292 • C (Fig.…”
Section: Characterization Of the Supported/unsupported Magnetite Nanosupporting
confidence: 91%
“…The exothermic signal at 516 • C is attributed to the transformation from maghemite to hematite (␣-Fe 2 O 3 ). These two thermal events are consistent with the previously reported phase-transformation temperature range of magnetite [41,43,44]. As compared to Mag, MagMt-P exhibits much weaker signals of the transformation from magnetite to maghemite, which begins at about 292 • C (Fig.…”
Section: Characterization Of the Supported/unsupported Magnetite Nanosupporting
confidence: 91%
“…The exothermic signal at 516 • C is attributed to the transformation from maghemite to hematite (␣-Fe 2 O 3 ). These two thermal events are consistent with the previously reported phase-transformation temperature range of magnetite [44][45][46]. As compared to Mag, MagDt-P exhibits weaker signals of the transformation from magnetite to maghemite, which begins at about 250 • C and finishes at ca.…”
Section: Characterization Of the Diatomite-supported/unsupported Magnsupporting
confidence: 91%
“…The fast weight loss of the samples at 120 or 115°C was most likely due to the evaporation of water and small molecules in the samples. In addition, the TGA curve of NIO‐M exhibited a slow weight loss between 115 and 247°C, which was consistent with the steady evaporation and volatilization of the surface adsorptive water on the nanoparticle surfaces and the subsequent loss of capillary water between the particles . When the temperature reached 284 and 457°C, the weight loss in NIO and NIO‐M reached 17.73 and 16.16%, respectively.…”
Section: Resultssupporting
confidence: 63%
“…This indicated that there are still a few zero‐valent iron nanoparticles in the NIO‐M even though the samples were not dried in a vacuum, which is consistent with the XRD and TEM characterization results. From 120 to 258°C, the DSC curve of NIO indicated a smooth decreasing trend, which was due to the steady evaporation and volatilization of the surface adsorptive water on the nanoparticle surfaces and the subsequent loss of the capillary water between the particles . Another exothermic event started at 288°C (higher than the previously reported 187°C for a pure magnetite sample ) and ended at approximately 388°C, and the event may correspond to the magnetite (Fe 3 O 4 ) to maghemite (γ‐Fe 2 O 3 ) transformation .…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation